2015
DOI: 10.1097/coc.0b013e31829a2954
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Initial Transperineal Template-guided Mapping Biopsy of the Prostate Gland

Abstract: TTMB appears to provide more detailed information about prostate cancer grade and location compared with standard 12-core biopsy scheme. This information may serve as a baseline reference for image-guided biopsy (ie, magnetic resonance imaging) regimens, may facilitate clinical decision making and aid in the appropriate selection of patients for active surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
1
18
0
3
Order By: Relevance
“…However, such a high prevalence has been seen by others when applying TTPM biopsies to this group of men (Bittner et al , 2015); thus, it is possible that existing thresholds for clinical significance might need to be raised (Bratt et al , 2015; Valerio et al , 2016). …”
Section: Discussionmentioning
confidence: 90%
“…However, such a high prevalence has been seen by others when applying TTPM biopsies to this group of men (Bittner et al , 2015); thus, it is possible that existing thresholds for clinical significance might need to be raised (Bratt et al , 2015; Valerio et al , 2016). …”
Section: Discussionmentioning
confidence: 90%
“…Using such a volume-adjusted stringent systematic saturation approach, the combination of the two biopsy methods did not have significant additional benefit. The detected overall cancer rates with 65% for all patients and 72, 45, and 81% for the primary biopsy cohort, the repeat biopsy cohort, and the surveillance cohort, respectively, are clearly compatible compared to other transperineal template-guided saturation (TTSB) or mapping biopsy studies (TTPM): for primary biopsy cohorts, detection rates of 54-76% have been reported using a mean amount of 19-54 cores [20][21][22][23] ; and for repeat biopsy cohorts, detection rates of 26-68% with a mean amount of 18-59 cores have been reported [21,22,[24][25][26][27][28][29] . In series in which TTPM biopsies was followed by RP, TTPM was highly accurate in detecting and excluding clinically significant disease [30,31] .…”
Section: Discussionmentioning
confidence: 68%
“…We used TTMB following a prior negative MRI-guided biopsy, as there was still a clinical indication of cancer. In published literature, cancer detection of TTMB in the primary setting and following a prior negative biopsy is 73% to 76% and 46% to 68%, respectively [14,15]. TTMB is rarely used as a primary biopsy technique but its high negative predictive value is often used to rule out significant cancer in patients with prior negative biopsy and prior to tissue-preservation management (AS and FT) [15].…”
Section: Discussionmentioning
confidence: 98%